2022
DOI: 10.1029/2021wr031788
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Behavior of Sand‐Silt Mixtures: Revisiting the Erosion Threshold

Abstract: Coastal sediments are usually mixtures of particles of various sizes, such as clay (<4 μm), silt (4-62.5 μm) and fine sand (62.5-500 μm), as well as organic matter (van Rijn, 2006). Classification of sediment fraction is defined by sediment size according to the Wentworth grain size scale. Sand-or sand-dominated mixtures are noncohesive and eroded particle by particle, whereas clay-dominated mixtures are cohesive and have a strong relationship between particles. Silt or silt-dominated mixtures with limited cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
0
14
3
Order By: Relevance
“…The observation that the sediment mobility increases when adding coarse silt to the bed is in line with what can be expected from experiments with gravel-sand mixtures, but opposes previous observations in laboratory experiments with sand-silt mixtures. and Yao et al (2022) observed that non-cohesive silt stabilizes the sediment bed, but at different concentrations (∼1.4% silt and >35%, respectively), whereas, in our experiments, even at 50% coarse silt the mobility of the sediment was increased. Interestingly, , whose experiments fall in the range of pore bridging (D coarse / D f ines = 5.5), explained the filling of pore space as a reason for increased stability of the bed due to reduced hyporheic flow, rather than a reason for increased mobility of the coarse fraction as found in gravel-sand experiments (Section 4.2.1).…”
Section: 22contrasting
confidence: 65%
See 1 more Smart Citation
“…The observation that the sediment mobility increases when adding coarse silt to the bed is in line with what can be expected from experiments with gravel-sand mixtures, but opposes previous observations in laboratory experiments with sand-silt mixtures. and Yao et al (2022) observed that non-cohesive silt stabilizes the sediment bed, but at different concentrations (∼1.4% silt and >35%, respectively), whereas, in our experiments, even at 50% coarse silt the mobility of the sediment was increased. Interestingly, , whose experiments fall in the range of pore bridging (D coarse / D f ines = 5.5), explained the filling of pore space as a reason for increased stability of the bed due to reduced hyporheic flow, rather than a reason for increased mobility of the coarse fraction as found in gravel-sand experiments (Section 4.2.1).…”
Section: 22contrasting
confidence: 65%
“…Yet, none of these studies discussed the potential impact of silt content on bedforms. This is an important research gap, because an increase in bed stability, as observed by and Yao et al (2022), could theoretically reduce bedform formation and growth due to a decrease in sediment transport, whilst 's suspensionload dominated high-efficiency regime would also mean suppression of bedform formation and growth, but then because bedload transport gets increasingly replaced by suspended load transport, which is incapable of forming bedforms. Clearly, the effect of silt in sand-silt mixtures on the resulting bedform geometry is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this part of our study show that the presence of cohesiveness in a fine‐grained sediment environment makes the empirical formula no longer applicable. It is worth noting that current laboratorial research uses similar strategies to modify empirical formulas and achieves comparable outcomes (Yao et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the influence of salinity on the erosion of kaolinite varies as a function of particle size, pH, and temperature (Hoomehr et al., 2018; Raudkivi & Hutchison, 1974). In addition, sediment mixtures of cohesive and non‐cohesive sediments display mechanical characteristics that contrast with pure clay (Van Ledden et al., 2004; Yao et al., 2022) and are beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 99%